Eliminatywizm i artefakty - Grygianiec, Mariusz (Filozofia Nauki, 2010)
The paper provides an answer to Paweł Garbacz's article Problem of Artefact's Existence, which is a critique of eliminativistic views presented in my book Identyczność i trwanie. Studium ontologiczne (Identity and Persistence. An Ontological Study). In the text crucial objections formulated by Garbacz are reconstructed and carefully discussed.